EKSPLORASI PERAN GURU DALAM PEMBENTUKAN KETERAMPILAN SOSIAL SISWA KELAS V DI SDN 65 KOTA JAMBI - Muhamad Wasito; Ahmad Hariandi; Ahmad Syarif (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Social skills are crucial aspects in elementary school students' development that influence their ability to interact, collaborate, and build positive relationships. This research aimed to describe the teacher's role in forming social skills of fifth-grade students at SDN 65/IV Jambi City, identify obstacles faced, find solutions, and identify social skills being developed. The research employed a qualitative approach with a case study design. Qualitative research methods emphasize meaning rather than generalization. Data collection was conducted through observation, interviews, and documentation with one fifth-grade homeroom teacher and six students as research subjects. Triangulation techniques were used for data validity, while data analysis used the Miles and Huberman model including data reduction, data display, and conclusion drawing. The results showed that teachers have essential roles through three main functions: (1) as educators who become role models and teach moral values, (2) as communicators who communicate effectively and involve parents, (3) as mediators who facilitate discussions and resolve conflicts. Obstacles encountered included external school environmental influences and students' individualistic attitudes. Solutions were implemented through social habituation, reward provision, and conflict resolution through dialogue. Teacher skills utilized included effective communication, empathy, collaborative guidance, role modeling, and positive reinforcement. This research aligns with Carl Rogers' Humanistic Theory and Albert Bandura's Social Cognitive Theory regarding the importance of role modeling in social learning.